Frequency and impact of midlife stressors among men and women with physical disability. Issue 15 (17th July 2019) - Terrill, Alexandra L.; Molton, Ivan R.
Abstract: Purpose: Middle-age may be a challenging time for people with physical disabilities as life demands, secondary symptoms such as fatigue, and risk for depression increase, yet little is known about types, levels, and impact of life stressors in individuals aging with disability. Our aims were to describe aging- and disability-associated life stressors, explore gender differences, and evaluate effects of resilience on adjustment to these stressors. Materials and methods: Longitudinal data analysis of self-report surveys completed by 541 middle-aged community-dwelling participants with long-term physical disability from baseline to 5-year follow-up. Results: 97% of participants endorsed one or more stressful life events (M = 8.2, SD = 4.9), all of whom endorsed at least one life stressor with a negative impact. Reporting more life stressors and having lower resilience were significantly associated with developing more depressive symptoms. Interaction analyses indicated that women developed more depressive symptoms as negative impact increased than men. Conclusions: Findings suggest that middle-aged individuals with physical disability experience a range of life stressors, many with negative impact. Women are at higher risk of depressive symptoms than men. Resilience may buffer against negative impact of life stressors on development of depressive symptoms. Targeted intervention to increase resilience, especially in women, may decrease risk of depression in persons aging with disability. Implications for Rehabilitation: Middle-age adults living with physical disability experience a number of aging- and disability-associated stressors that can have a negative impact and contribute to depression. Women aging with disability who experience more negative impact from life stressors may be more vulnerable to developing depression. Providing interventions that enhance resilience when faced with life stressors could prevent development of depression.